2015
DOI: 10.1039/c5md00159e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unusual isoxazoline containingβandγ-dipeptides as potential glutamate receptor ligands

Abstract: Unconventional beta and gamma dipeptides as tools to investigate the iGluR binding domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The two enantiomers of compound 1 were obtained starting from the corresponding ethyl esters recently described by us (Tamborini et al, 2015 ). Racemate (±)- 2 (Conti et al, 2006 ) was synthesized in a flow chemistry reactor exploiting the 1,3-dipolar cycloaddition reaction of N -Boc-3-pyrroline with ethoxycarbonyl formonitrile oxide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two enantiomers of compound 1 were obtained starting from the corresponding ethyl esters recently described by us (Tamborini et al, 2015 ). Racemate (±)- 2 (Conti et al, 2006 ) was synthesized in a flow chemistry reactor exploiting the 1,3-dipolar cycloaddition reaction of N -Boc-3-pyrroline with ethoxycarbonyl formonitrile oxide.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we investigated the conformational behavior of both the enantiomers of the bicyclic unnatural γ amino acid 4,5,6,6a-tetrahydro-3a H -pyrrolo[3,4- d ]isoxazole-3-carboxylic acid 1 , obtained starting from the corresponding ethyl esters recently described by us (Tamborini et al, 2015 ). Compound 1 is a conformationally constrained dipeptide analog and, in principle, it could substitute two amino acids in a peptide chain.…”
Section: Introductionmentioning
confidence: 99%
“…The enatiomeric mixture was separated using Chiral Semi-Preparative-HPLC. [34] Each enantiomer was then inserted into model peptides. NMR, FT-IR, CD and molecular modeling studies indicated that the dipeptide Gly/(+)-36 is able to stabilize a αturn conformation, due to H-bond between C=O Gly (i) and NH of amide protecting group (i + 4).…”
Section: Gamma Aasmentioning
confidence: 99%
“…In particular, the 3‐isoxazolidinone scaffold is present in the natural amino acid Tricholomic acid ( 24) and in various derivatives active on the glutamate neurotransmission system ( 25 and 26 , Scheme 10). [52,68,95–99] …”
Section: Reactivity Of 3‐bromo‐45‐dihydroisoxazolesmentioning
confidence: 99%
“…Moreover, the replacement of bromine with hydroxy or alkoxy moieties has been employed for the synthesis of Muscarone analogues, [78] neuroactive molecules [70,100–102] and antiparasitic compounds [18] . Aliphatic alcohols can be easily converted in situ in the corresponding alkoxy anions, using a base such as K 2 CO 3 , [18,70,79,82,102] Cs 2 CO 3 [88,103] or NaH [31,97,101,102] . These alkoxy species are nucleophilic enough to attack the C3 carbon and displace the bromine to give the 3‐alkoxy‐Δ 2 ‐isoxazolines.…”
Section: Reactivity Of 3‐bromo‐45‐dihydroisoxazolesmentioning
confidence: 99%